Enhancing the near decoupling property of closed-loop control systems through external constant feedback loop. (September 2018) - Jetto, L.; Orsini, V.
Highlights: A new near decoupling control scheme is proposed. Possibly uncertain plants are considered. The proposed method consists of an easy to use procedure based on the notion of diagonal dominance. A twofold feedback control structure is considered. Abstract: This paper deals with the near decoupling problem for linear, possibly uncertain plants. The new proposed decoupling scheme is given by a closed-loop control system endowed with a twofold feedback loop. The internal feedback action is designed to satisfy the usual control requirements, the purpose of the external feedback loop is to yield an overall control system with an enhanced degree of approximate decoupling, still keeping internal stability. In this way, the usually complex design procedure for the simultaneous achievement of common control specifications and near decoupling is decomposed into two independent simplified sub-problems. Two examples taken from the relevant literature, are given to show the effectiveness of the proposed approach.